(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to clarify the role of digital intelligence in enhancing outstanding performance, with a focus on the programs used by the University of Babylon in the application of the level of performance and this digital program is a combination of information systems and tools that contribute to the digitization of educational institutions and their transformation into smart universities, and their contribution to raising the efficiency and quality of performance in Iraqi universities and raising their global ranking, as well as what leads to it in the development of universities and the formula of international cooperation through the strengthening of international partnerships. The importance of this study comes to measure the extent of the combination of relationships between the variables mentioned in this study, digital intelligence in its dimensions (digital efficiency, digital security, digital empathy, digital communication, digital rights) and outstanding performance in its dimensions (excellence of leaders, excellence of subordinates, excellence of organizational culture, improvement of services provided, increase job satisfaction of workers) and its application in the University of Babylon research sample, as intelligence Digital is one of the factors affecting the enhancement of performance, in educational institutions and is critical to ensure the provision of the best modern ways to serve the community where universities in the era of globalization and the business economy and knowledge market competitive market and knowledge race between international universities and Iraq in particular has relied on the researcher in addressing his research on the descriptive approach to address the conceptual aspect and the analytical approach in dealing with the applied side of the research and used the questionnaire form as a tool to collect primary data.